A clinical case of cardioprotective therapy with exogenous phosphocreatine during chemotherapy and anti HER2-neu therapy in a patient with breast cancer - Andrey L. Pylev; Vyacheslav A. Lisovoy; Olga S. Kozlova (LLC "MEDIAFORMAT", 2023)
The authors describe a clinical observation of cardiotoxicity of anticancer targeted therapy in a young patient with HER2neu-positive breast cancer. The results of instrumental examinations demonstrating manifestations of cardiotoxicity are presented. The development of cardiovascular side effects against the background of anticancer treatment requires the appointment of cardioprotective therapy. Exogenous phosphocreatine (Neoton) can be considered as a cardioprotective agent, demonstrating efficacy in reversing cardiotoxicity induced by anti-HER2neu therapy.